The Struggle for Employment: Educated Class between the World Wars in Colonial United Provinces - Chandra, Gautam; ., Pranjali (Journal of Posthumanism, 2024)
United Provinces witnessed striking educational growth in 1920s with the establishment of Banaras Hindu University, Aligarh Muslim University, Lucknow University, Kashi Vidyapeeth and other professional institutes. After the number of students started to increase, the struggle for employment became evident and the British government appointed a Departmental Committee under the Presidentship of Minister of Education, Rai Rajeshwar Bali, in 1927 to suggest solutions for unemployment among the educated class. Subsequently, the 1931 census tried to calculate the number of educated unemployed and a United Provinces Unemployment Committee was set up by the colonial government under the Chairmanship of Tej Bahadur Sapru. However, the historiography is silent regarding the struggle for employment of the educated class in United Provinces, especially during the period between World Wars. Viewed in this context, the present article explores the progress of education and tries to locate the struggling career of educated class and unemployment in colonial United Provinces.